Assessing and managing earthquake risk : geo-scientific and engineering knowledge for earthquake risk mitigation--developments, tools, techniques - Roca, Antoni; Goula, Xavier; Oliveira, Carlos Sousa (Dordrecht, The Netherlands : Springer, 2006)
08